ANALYSIS OF THE LEVEL OF MATHEMATICS LEARNING PERSEVERANCE OF UPPER GRADE STUDENTS IN ELEMENTARY SCHOOL - Muhammad Awal Awal Nur; Andika Marsuki; Muhammad Idris Djafar; Luthfiyatul Muniroh (Universitas Muhammadiyah Lampung, 2026)
Mathematics is often perceived as a difficult, anxiety-inducing, and challenging subject by many students, which in turn affects their learning achievement. Several studies have shown that students frequently experience mathematics anxiety and low self-confidence when engaging with mathematical tasks, leading to decreased performance and motivation to learn. The purpose of this study was to examine and provide evidence on the level of students perseverance in learning mathematics. The findings are expected to help teachers and schools develop strategies that foster students perseverance, enhance engagement, and ultimately improve mathematics achievement. This research is descriptive quantitative with a survey approach. This research was conducted in March 2025. The population in this study were all students in grades IV, V and VI at SD Negeri 23 Jeppe'e, Bone Regency with a total of 60 students. The sample was selected by random sampling with a sample size of 30 students. The research instrumentused was the Mathematics Learning Persistence Scale, which consists of 28 valid statements with a Cronbach's alpha coefficient of 0.78. Data collection was done by distributing math learning perseverance scale and data analysis technique was descriptive statistics. The results of the study show that the perseverance of students in learning mathematics at SD Negeri 23 Jeppe, Bone Regency, is in the moderate category with an average score of 85.8. This shows that most students have a fairly good endurance in dealing with math learning difficulties, but there is still a tendency to give up easily when encountering challenging math problems. Teachers are advised to design learning activities that encourage students' perseverance, for example by using the Problem-Based Learning or Project-Based Learning approaches, which require students to repeatedly solve problems until they succeed.